Modelling Progressive Collapse in Steel Structures - JANSSENS, VICTORIA MARIA (Department of Civil, Structural and Environmental Engineering, 2012)
The partial collapse of the Ronan Point apartment tower in 1968 was a pivotal event with regard to the way structural engineers considered progressive collapse. This event spurred a significant amount of research into the prevention of disproportionate collapse and prompted the Fifth Amendment to the UK Building Regulations. As a result, the possibility of structural collapse was considered for the first time in a regulatory document. From this point on, buildings were required to exhibit a minimum level of robustness to resist progressive collapse. Following the recent terrorist attacks on the Alfred P Murrah Federal Building, in 1995, and the World Trade Centre, in 2001, interest in this subject appears to have reached a peak. Additionally, these events have highlighted the increased threat of terrorism worldwide and the need to consider hazards (e.g. explosions and detonations) that may not have been viewed as significant in the past.A collapse of this nature can be triggered by many causes: including design and construction errors, as well as loading conditions with a low probability of occurrence (e.g. gas explosions, vehicular collisions). However, the unforeseen nature of these events presents the designer with a significant challenge when trying to improve structural safety. As building designers cannot possibly design for every hazard that a building may be subjected to in its lifetime, a general design approach is required to account for the risks associated with low-probability high-consequence events. In view of this, a number of design methods to improve structural robustness have been developed that are independent of the loading event: namely, the notional element removal and specific local resistance methods. The primary objective of this research is to develop an analysis program that is capable of modelling the complex structural behaviour associated with progressive collapse. This program is based on the finite element method of analysis and implements the notional element removal method using three different types of analysis, of increasing complexity: linear static, nonlinear static and nonlinear dynamic analysis. The effects of material nonlinearities are modelled using lumped plastic hinges and geometric nonlinearities are accounted for by regularly updating the structural matrices to include the displaced shape of the structure. In order to compute the time-varying response of the structure following the loss of a member, a fourth order Runge-Kutta routine is implemented. Meanwhile, viscous damping effects are incorporated in the dynamic analysis algorithm using Rayleigh damping theory. A key feature of the program is that it is capable of following the sequence of failures that occur during a progressive collapse. In order to achieve this, all members are periodically checked for failure: this may be due to the formation of an unstable mechanism, instability of a member or exceeding the capacity of a member. Following the development of this program, a number of case studies are undertaken to investigate the response of steel moment-resisting frames following the loss of a primary load-carrying member. A comparison of the three analysis routines implemented in this program is performed, the results of which demonstrate the conservative nature of linear static analysis. Additionally, the importance of dynamic effects when considering progressive collapse is illustrated. Furthermore, an investigation of the influence of damping shows that the level of damping assumed has a notable influence on the response of the structure. This is contrary to the often cited assumption that the effects of damping will be negligible in progressive collapse and therefore raises some interesting research questions. Finally, a framework is developed for assessing the consequences of building failure, due to an unidentified hazard. This is intended to assist designers when undertaking a risk assessment to assess the sensitivity of a building to progressive collapse and could be employed, together with the analysis program developed, to quantify the risk for a structure. In developing this framework, a multi-disciplinary approach is adopted. In view of this, a detailed overview of consequence assessment is provided, drawing from a wide range of subject areas and focusing on their relevance to building failures as a result of an unidentified hazard. The multi-dimensional and variable aspects of the `cost-of-failure? are discussed and a categorisation of failure consequences, as well as associated models for their quantification, is developed.
PUBLISHED
Keywords: Steel structures